Psychometric Validation of the UCLA Loneliness Scale Version 3: Evidence for a Six-Factor Structure Among Science Teachers - Novi Hidayat; Farah Fadilah Hasyim; Denny Hariyanto; Muhammad jayyid; Dikut Affan Aryansyah (Integrated Science Education Journal, 2026)
Purpose of the study: This study aimed to evaluate the construct validity and factor structure of the Indonesian version of the UCLA Loneliness Scale Version 3. Methodology: A quantitative methodological validation design was conducted with 132 Indonesian science teachers selected through purposive sampling. The instrument was culturally adapted through forward translation, back translation, expert content validation, and pilot testing. Construct validity was examined using Exploratory Factor Analysis (EFA), including the Kaiser–Meyer–Olkin (KMO) measure, Bartlett's Test of Sphericity, Measure of Sampling Adequacy (MSA), and Principal Component Analysis (PCA) with Varimax rotation. Internal consistency was assessed using Cronbach’s alpha. Main Findings: The Indonesian version demonstrated satisfactory psychometric properties. The KMO value (0.795) and Bartlett's Test of Sphericity (p < .001) confirmed the suitability of the data for factor analysis. All items achieved MSA values and factor loadings above 0.50. EFA identified a six-factor structure, supporting the multidimensional nature of loneliness among Indonesian teachers and providing evidence of acceptable construct validity. Novelty/Originality of this study: The findings indicate that the Indonesian version of the UCLA Loneliness Scale Version 3 is a valid and reliable instrument for assessing teacher loneliness. This study provides the first psychometric validation of the scale among Indonesian teachers. The validated instrument offers practical implications for educational psychology research, psychological assessment, and the development of interventions to promote teachers' psychological well-being.